Pelatihan Pengolahan Sampah di Bank Sampah Koperasi Warga Sadaya (KOWASA) Kecamatan Jonggol Bogor Jawa Barat - Irwan Siagian; Bondan Bondan; Hanum Nurul Aulia (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The waste problem is something that is common to all parties. Garbage is a thing that coexists with human life, almost all human activities produce garbage. The problem is how waste can be handled and minimized, because there are many types of waste. Starting from the types of organic, inorganic, and B3. If it is organic waste, it will be easier to process or process by itself. However, often the problem is when the waste is of an inorganic type, such as plastic. Plastic material we know, is a difficult item to decompose. The problem of partners is often faced, namely the difficulty of finding a collaborative partner in distributing the collected waste. This waste itself is produced from residents in the community of Sukasirna Village. Garbage is indeed a source of disasters and environmental problems. However, if the waste management is managed properly and properly by utilizing qualified resources, it will generate income for the manager. We see that the waste management managed by the Garbage Bank is not optimal. Therefore, as a community service team, we provide counseling on how to manage both organic and inorganic waste optimally so that the waste produced is not only a source of environmental problems but can generate income. Our service partner is one of the KOWASA Waste Bank (Koperasi Warga Sadaya) located in the village of Sukasirna, Jonggol District, Bogor Regency. The solution we provide to our service partners is to conduct discussion activities by sharing information and questions and answers about problems faced by partners online. The techniques used in community service are as follows: a, direct observation, namely visiting partner locations, b. conduct community service with a system of education and questions and answers regarding organic and inorganic waste management, c. provide training in the form of skills in managing organic and inorganic waste, d. Conducting evaluation and shering together to find an agreement in waste management so that it does not become a problem for the environment. The output targets to be achieved in this service activity are as follows: a. people who have skills, b. high-value products from waste raw materials